The regulatory effects of p53 on the typical and atypical ferroptosis in the pathogenesis of osteosarcoma: A systematic review - Wang, Linfeng; Pan, Su (Frontiers in Genetics, 2023)
Study background: As a rare condition, osteosarcoma affects approximately 3% of all cancer patients. Its exact pathogenesis remains largely unclear. In the present review, we investigated the role of p53 in regulating typical and atypical ferroptosis in osteosarcoma. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and the Patient, Intervention, Comparison, Outcome, and Studies (PICOS) protocol were used in the initial search. The literature search was performed in six electronic databases, including EMBASE, Cochrane library of trials, Web of Science, PubMed, Google Scholar, and Scopus Review, using keywords connected by Boolean operators. We focused on studies that adequately defined patient profiles described by PICOS. Results and discussion: We found that p53 played fundamental up- and down-regulatory roles in typical and atypical ferroptosis, resulting in either advancement or suppression of tumorigenesis, respectively. Direct and indirect activation or inactivation of p53 down-regulated its regulatory roles in ferroptosis in osteosarcoma. Enhanced tumorigenesis was attributed to the expression of genes associated with osteosarcoma development. Modulation of target genes and protein interactions, especially SLC7A11, resulted in enhanced tumorigenesis Conclusions: Typical and atypical ferroptosis in osteosarcoma were regulatory functions of p53. The activation of MDM2 inactivated p53, leading to the down-regulation of atypical ferroptosis, whereas activation of p53 up-regulated typical ferroptosis. Further studies should be performed on the regulatory roles of p53 to unmask its possible clinical applications in the management of osteosarcoma.